Dependence of blood coagulation activity on temperature in cows in vitro - L. L. Fomina; D. I. Berezina; T. S. Kulakova; K. E. Modanova (Аграрная наука Евро-Северо-Востока, 2024)
The paper presents the results of a study on how temperature affects the coagulation and anticoagulation processes in the hemostasis system of cows. The purpose of this work was to study the coagulation parameters of the blood of Ayrshire cows with hypo-, normo- and hyperthermia "in vitro", as well as to evaluate the possibility of using a coagulometer to characterize the activity of hemostasis and use hemostatic reactions in cattle as models for human medicine. The study was carried out in the Vologda region. The following parameters of the coagulation profile were analyzed: thrombin time (TT), prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen and antithrombin III (AT-III) activity. Results showed that at 43 °C hypercoagulation of the blood occurred, which in clotting methods manifests itself as an acceleration of TT by 61 % (27 sec), PT by 29 % (10 sec), a prolongation of APTT by 38 % (25 sec) and a decrease in Antithrombin III activity by 51 % (5 sec) compared with normothermia. At 18 °C, hypocoagulation was detected, accompanied by an elongation of all indicators characterizing the rate of clot formation: TT by 10 % (5 sec), PT by 61 % (55 sec), APTT by 83 % (289 sec). Fibrinogen activity decreased by 82 % (106 sec), and AT-III activity increased by 85 % (56 sec) compared to normothermy. The correlation between hemostasis parameters and the temperature factor can be characterized as negative moderate (APTT), noticeable (TV, fibrinogen) and close (PT, AT-III). Using a medical coagulometer caused reaction rates to differ significantly from those occurring at the body temperature of these animals when studying the coagulation mechanisms of cows. This does not allow to recommend this device for an adequate assessment of hemostatic reactions in cattle.